Evaluating CXCR6 and its ligand CXCL16 as biomarkers for lupus organ involvement: a mini review and brief research report - Kernizan, Faradia; Dave, Himanee; Rossetti, Victoria; Frey, Cheri; Richmond, Jillian M. (Frontiers in Lupus, 2025)
Cutaneous lupus erythematosus (CLE) is a group of skin disorders where the immune system attacks skin cells. CLE can affect people who have systemic lupus erythematosus, or can occur independently. In prior studies, CXCL16 and its primary receptor, CXCR6, have been shown to be elevated at the RNA or protein level in different organs that are affected by lupus. In this systematic review, we sought to understand whether CXCR6 and its ligand CXCL16 could serve as biomarkers for lupus skin or other organ involvement. Our search strategy and protocol are registered on Prospero under # CRD42024583076. CXCL16 was shown to be a biomarker of lupus nephritis and disease activity in both urine and serum samples in multiple studies. CXCL16 was also elevated in cerebrospinal fluid in neuropsychiatric lupus patients as well as other autoimmune brain conditions. Last, we queried publicly available datasets and our own datasets to evaluate expression of CXCR6 and CXCL16 in lupus skin. CXCR6 but not CXCL16 was enriched in lupus skin across multiple datasets and model organisms. Taken together, our study corroborates the CXCR6 chemokine family as a potential biomarker of lupus organ involvement.